Hubungan antara Psychological Capital dan Job Satisfaction pada Karyawan Surabaya melalui Work Engagement - Charokatul Islach; Eben Ezer Nainggolan; Sayidah Aulia Ul Haque (CV. ITTC INDONESIA, 2026)
This study examines the relationship between psychological capital and job satisfaction through work engagement among employees in Surabaya. A quantitative correlational design was employed. Participants consisted of 399 active employees from various work sectors in Surabaya selected using convenience sampling. Data were collected using three instruments: the 12-item Psychological Capital Questionnaire, the 17-item Utrecht Work Engagement Scale, and the 36-item Job Satisfaction Survey. Data analysis was conducted using linear regression and mediation analysis based on Ordinary Least Squares. The results indicate that psychological capital does not directly influence job satisfaction. Psychological capital influences work engagement, and work engagement influences job satisfaction. Mediation analysis confirms that work engagement fully mediates the relationship between psychological capital and job satisfaction. These findings indicate that job satisfaction is formed through work engagement rather than directly from internal psychological resources.